Fabrication of a silver nano powder embedded kraton polymer actuator and its characterization. Issue 111 (26th October 2015) - Khan, Ajahar; Inamuddin; Jain, R. K.; Naushad, Mu.
Abstract : A novel silver nano powder (Ag Pw) embedded kraton (KR) ionic polymer actuator was fabricated. Abstract : A novel silver nano powder (Ag Pw) embedded kraton (KR) ionic polymer actuator was fabricated. The KR–Ag-Pw ionic polymer metal composite (IPMC) membrane was prepared by a solution casting method. The IPMC membrane shows good electro-mechanical, ion exchange, water retention (WR) and proton conductivity (PC) properties which are responsible for the high performance of the ionic polymer actuator. The physicochemical properties of the KR–Ag-Pw ionic polymer actuator were determined using X-ray diffraction, Fourier transform infra-red spectroscopy (FTIR), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA) studies. After applying a voltage (0–3.5 V DC), the maximum bending behaviour is achieved up to 17 mm. By constructing a multi KR–Ag-Pw IPMC finger based gripper, it is proved that this kind of actuator has potential in robotic applications.